An all-in-one pipeline for the in vitro discovery and in vivo testing of Plasmodium falciparum malaria transmission blocking drugs - Nicolas M. B. Brancucci; Christin Gumpp; Geert-Jan van Gemert; Xiao Yu; Armin Passecker; Flore Nardella; Basil T. Thommen; Marc Chambon; Gerardo Turcatti; Ludovic Halby; Benjamin Blasco; Maëlle Duffey; et al. (Nature Communications)
Abstract Elimination of malaria will require new drugs with potent activity against Plasmodium falciparum mature stage V gametocytes, the only stages infective to the mosquito vector. The identification and comprehensive validation of molecules active against these quiescent stages is difficult due to the specific biology of gametocytes, challenges linked to their cultivation in vitro and the lack of animal models suitable for evaluating the transmission-blocking potential of drug candidates in vivo. Here, we present a transmission-blocking drug discovery and development platform that builds on transgenic NF54/iGP1_RE9Hulg8 parasites engineered to conditionally produce large numbers of stage V gametocytes expressing a red-shifted firefly luciferase viability reporter. Besides developing a robust in vitro screening assay for the reliable identification of stage V gametocytocidal compounds, we also establish a preclinical in vivo malaria transmission model based on infecting female humanized NODscidIL2Rγnull mice with pure NF54/iGP1_RE9Hulg8 stage V gametocytes. Using whole animal bioluminescence imaging, we assess the in vivo gametocyte killing and clearance kinetics of antimalarial reference drugs and clinical drug candidates and identify markedly different pharmacodynamic response profiles. Finally, we combine this mouse model with mosquito feeding assays and thus firmly establish a valuable tool for the systematic in vivo evaluation of transmission-blocking drug efficacy.